Isotopic Evidence for the High Contribution of Wintertime Photochemistry to Particulate Nitrate Formation in Northern China. Issue 22 (22nd November 2021) - Zhang, Zhongyi; Jiang, Zhuang; Guan, Hui; Liang, Yue; Zheng, Nengjian; Guo, Wei
Abstract: Stable isotopic constraint and observationally coupled atmospheric chemistry model are two robust means to identify the oxidation mechanisms for atmospheric particulate nitrate (NO3 − ) production. However, large discrepancies between the two approaches have been noted in the heavily polluted environments of North China Plain (NCP). Herein, daily PM2.5 samples ( n  = 418) were collected at five urban cities across NCP during the winter of 2017–2018; the ionic species (e.g., NO3 − and methanesulfonic acid: MSA) and the dual‐isotopic signatures of NO3 − were quantified. In this study, we revisited the O isotopic signatures of atmospheric O‐bearing molecules, especially that of OH radical in accordance with the up‐to‐date field measurements conducted in NCP regions. In brief, the δ 18 O‐OH was determined by the competition between the OH loss reaction rate and its isotopic equilibration reaction with H2 O. Our improved isotopic results suggested that the daytime OH oxidation pathway was as important as the nocturnal channels in wintertime nitrate production in NCP (46.4% vs. 53.6%), whereas the exceedingly high loadings of NO3 − in haze days were attributed to the heterogeneous chemistry of N2 O5 hydrolysis. Chemical analysis also confirmed the importance of active photochemistry in secondary components production, as the MSA (a photooxidation product) linearly correlated with the NO3 − ( R 2  = 0.86, p  < 0.05). Our preliminary results compared well with the recent model simulations (e.g., sophisticated 3D model and observationally constraint model). To alleviate the winter haze in NCP, future emission regulations should aim to reduce the photochemical oxidants, particularly their precursors of NO x and VOCs simultaneously. Key Points: The predicted δ 18 O‐OH values are on average of −29.9 ± 8.2‰ and +13.5 ± 1.4‰ in clean and polluted days, respectively The determined PM2.5 nitrate is significantly and positively correlated with MSA ( R 2  = 0.86, p < 0.05), a potential photooxidation indicator Results suggest the wintertime photochemistry plays an important role in the production of particulate nitrate